THE IMPLEMENTATION OF THE BRAIN BASED LEARNING MODEL WITH THE PHONICS METHOD ASSISTED BY FLASH CARD ON THE BEGINNING READING ABILITY OF GRADE 1 STUDENTS AT MI NU TARBIYATUL ISLAM - Nurul Azizah; Suci Herwani (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
Early reading instruction is a fundamental step in developing elementary school students' literacy skills. The learning process needs to be tailored to the characteristics and workings of the child's brain to make learning more effective and meaningful. One approach that can be applied is the Brain-Based Learning model with the Flash Card-assisted phonics method, which involves multisensory activities in introducing letter sounds and letter symbols. This study aims to describe the application of the Brain-Based Learning model with the Flash Card-assisted phonics method in teaching reading to first-grade students at MI NU Tarbiyatul Islam. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that the application of this learning model helped students recognize letter sounds, connect letter sounds with letter symbols, and read syllables and simple words. In addition, students appeared to be more active participants and the learning atmosphere became more interesting and conducive. Thus, the application of Brain-Based Learning with the Flash Card-assisted phonics method can support the early reading learning process in elementary school students.